Second Language Acquisition and Writing Proficiency of Secondary School Students in Ogun State - Obi, Modupeola (African Journal of Behavioural and Scale Development Research, 2022)
This study examined the direct relationship between Second Language Acquisition (SLA) and writing proficiency of the students in some selected secondary schools in Ogun state. There are twenty Local Government Areas in Ogun state and three (3) of them were randomly selected for the study. A school was randomly selected from each local government and fifty scripts were randomly picked from the scripts of intact classes of SS II students, given the test in each school. A narrative essay topic was given to test the expression of the students. The errors were analysed to determine the pattern of errors that featured in the students’ writing using Error Analysis process. The problematic areas in students’ writing: Content, Organisation, Expression and Mechanical Accuracy were highlighted. It was concluded that writing proficiency in English Language enhances academic performance. It investigated the variation and problems in the SLA ( in this case the acquisition of English language) among Secondary School II Students in some selected secondary schools in Abeokuta, Ogun State as well as the implication, if any of such variation and problems for writing proficiency for learning. The focus of this paper is the influence of writing proficiency in Second Language (L2) of Nigerian students, their levels of competence in the second language and the relationship if any, in their cognitive achievement. The study revealed very few students (12%) were able to write the required 450 words. However, majority (53.4%) showed comprehension of the essay topic. The mistakes were recognized. In as much as composition writing is essential for a credit pass in English studies, which enhances performance in other subjects, there is need for concrete intervention to reduce in equality in writing proficiency of the students in secondary schools in Ogun state, Nigeria.